Pengaruh Hypnobreastfeeding Terhadap Tingkat Kecemasan Ibu Menyusui Pada Ibu Post Partum Sectio Caesarrea Dalam Meningkatkan Produksi ASI Di RS. Simpangan Depok - Anggita Anggita; Marisca Agustina; Elvie Tresya (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Introduction: This study highlights the level of anxiety of breastfeeding mothers in post partum caesarean section mothers. The cause that can influence the success of breastfeeding is the mother's psychological changes, mothers who give birth using the Sectio Caesarea method have a higher level of anxiety than mothers who give birth spontaneously. The importance of breast milk for babies contains the most optimal nutritional content to provide immune protection for the baby, for this reason hypnobreastfeeding intervention is given which is expected to reduce the level of maternal packaging. Objective: The aim of this research is to determine the effect of Hypnobreastfeeding on the level of anxiety of breastfeeding mothers in post partum sectio caessarea mothers in increasing breast milk production in hospitals. Depok intersection. Method: This research uses a quasi-experimental design with a one group pretest-posttest design without control group. The data collection method involved using the Hamilton Rating Scale For Anxiety (HARS) questionnaire to measure students' anxiety levels before and after the hypnobreastfeeding intervention. This study aims to assess the effect of hypnobreastfeeding on the anxiety level of breastfeeding mothers in post partum mothers. Results: The results of the research obtained a P-valeu value of 0.000 p < 0.05 which states that the Ha hypothesis was accepted and H0 was rejected, thus there was a significant change between before and after the hypnobreastfeeding intervention on changes in anxiety levels.